BELARUSIAN PARLIAMENTARY ELECTION IN 2019 - Czwołek, Arkadiusz; Kołodziejska, Julia (The Copernicus Journal of Political Studies, 2021)
In 2019 a snap election was held to the bicameral National Assembly of the Republic of Belarus. The election was fully controlled by the authorities. Numerous cases of election law violations were recorded by independent observers. The intensity of the election campaign was low and the candidates were not guaranteed equal access to the media. As in the previous parliamentary election, mainly “nonpartisan” candidates loyal to the regime and several representatives of pro-regime parties were elected. No candidate from the political opposition gained a seat in the new parliament. According to ODIHR/OSCE’s assessment, the 2019 Belarusian parliamentary election did not meet international standards.